A study on weight-on-bit data correction method of a near-bit measuring tool. (January 2019) - Xu, Xiaofeng; Meng, Yingfeng; Liu, Yonghui; Ji, Yueying
The real weight on bit is difficult to observe or estimate in highly deviated wells and extended-reach wells since complex loads are acted on drill string. Near-bit measurement while drilling tools, which are generally used to address this issue, can only measure axial forces based on axial strains instead of the real WOB. Axial forces on near-bit drill string are mainly controlled by buoyancy force of drilling fluid, circulating pressure, and other factors. To some extent, the measured data can be corrected by force analysis. It should be noted that experiments must be conducted to study the influences of differential pressure and temperature on measured WOB data of near-bit measuring tool. This article presents calculating method of real WOB via correction of measured data, based on force analysis of a self-developed near-bit measuring tool and experiments on influences of differential pressure and downhole temperature. Field test indicates that higher deviation angle will lead to a greater difference between real WOB and the indicated value at wellhead. Multi-well testing data verification indicates that this method is effective and reliable in extracting real WOB, and helpful to accurately identify the running state of bottom-hole assembly.